EMERGENCE OF ABRUPT GRAVEL TO SAND TRANSITIONS ALONG RIVERS THROUGH SORTING PROCESSES - Ferguson R.I. (My University, 2003)
Gradual downstream fining along gravel-bed rivers is often followed by a relatively abrupt change to a sand bed. This has usually been explained by the breakdown of pebbles of certain lithologies to sand, but it is not restricted to particular rock types and can occur over distances too short for significant abrasion. An alternative explanation is that as shear stress declines downstream, size sorting is enhanced through nonlinearities and thresholds in bedload transport and deposition mechanisms. This hypothesis is tested by numerical modeling of an idealized channel with a mixed gravel and sand bed. Abrupt and persistent gravel fronts with associated breaks of slope develop from a range of smooth initial states when a new initial-motion equation is used, but not with a conventional equation. The results suggest an emergent phenomenon, but one that is sensitive to process specification rather than initial or boundary conditions.
Keywords: geomorphology; modeling; gravel front; bedload transport